Hubungan Pola Pemberian Makan dengan Kejadian Stunting pada Anak Usia 24-59 Bulan - Hakim, Nuraini; Yuningsih, Yuningsih; Fani, Adzra (Universitas Baiturrahim, 2025)
Irreversible malnutrition in children can lead to growth disorders, including stunting. Factors that may contribute to stunting in toddlers are maternal and antenatal care, the home environment, breastfeeding practices, and toddler feeding patterns. The purpose of this study was to identify the relationship between feeding patterns and stunting in children aged 24-59 months. This study used a descriptive design with a cross-sectional approach, and data were analyzed using univariate and bivariate tests (chi-square tests). The sample used was 109 mothers with toddlers. The study was conducted in the Kelapa Dua area of Tangerang Regency from February to May 2025. The results of this study showed that 55 (50.45%) respondents implemented responsive feeding patterns, and 82 (75.2%) toddlers experienced stunting. The chi-square test results showed no relationship between feeding patterns and stunting in children aged 24-59 months with a p-value > 0.05. The conclusion is that there is no relationship between feeding patterns and stunting.